2021
DOI: 10.3390/met11050831
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Laser Welding of Al Ribbon to Cu Sheet: Weldability, Microstructure, and Mechanical and Electrical Properties

Abstract: The pulsed laser welding of Al ribbon to Cu sheet was investigated for the electrical interconnections in power electronic modules. The various experimental conditions with the different laser powers, scan speeds, and heat inputs were employed for obtaining the defect-free Al/Cu joints. During the Al/Cu laser welding, the intermetallic compounds were formed in the welding zone. An electron probe microanalyzer and transmission electron microscopy confirmed the phases of intermetallic compounds, which were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Al sheet is widely selected as the top material to irradiate by the laser beam because of its relatively high absorption to laser radiation (1030 nm) and low meting point (660 o C) in comparison to Cu. To obtain a good joint with Al to Cu is to irradiate laser from Aluminum (Al) to control the weld depth and mixing of Cu in Al [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Al sheet is widely selected as the top material to irradiate by the laser beam because of its relatively high absorption to laser radiation (1030 nm) and low meting point (660 o C) in comparison to Cu. To obtain a good joint with Al to Cu is to irradiate laser from Aluminum (Al) to control the weld depth and mixing of Cu in Al [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Cu-based filler, the weld zone exhibited a uniform structure characterized by the presence of the Cu solid solution phase and exhibited the highest tensile strength, reaching up to 80% of the tensile strength of pure copper. W. S. Shin et al [7]examined pulsed laser welding of aluminum to copper sheets and found that electron probe microanalysis and transmission electron microscopy confirmed the presence of intermetallic compounds, including Al4Cu9, Al2Cu, and AlCu. C. Zhang et al [4] investigated the diffusion bonding of Cu/Ni-based superalloys at 900°C for 1 hour under a bonding pressure of 10 MPa and observed that failure occurred in the Cu superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the brittle intermetallic compounds (IMCs) are easily formed, which seriously deteriorates the mechanical properties and the conductivity of the Al/Cu joints [8,9]. In the present study, different welding methods, in case of diffusion bonding (DB) [10], brazing [11,12], friction stir welding (FSW) [13][14][15], laser welding [16], and explosion welding (EW) [17,18], have been proved to be an alternative method in joining Al and Cu. ese studies have shown that it was inevitable to form the hard and brittle Al x Cu y phases such as Al 2 Cu, AlCu, Al 4 Cu 9 , and Al 3 Cu 4 on the interface of Cu/Al joints.…”
Section: Introductionmentioning
confidence: 99%